Invasive Fungal Disease After Chimeric Antigen Receptor-T Immunotherapy in Adult and Pediatric Patients - Paschalis Evangelidis; Konstantinos Tragiannidis; Athanasios Vyzantiadis; Nikolaos Evangelidis; Panagiotis Kalmoukos; Timoleon-Achilleas Vyzantiadis; Athanasios Tragiannidis; Maria Kourti; Eleni Gavriilaki (Pathogens)
Invasive fungal diseases (IFDs) have been documented among the causes of post-chimeric antigen receptor-T (CAR-T) cell immunotherapy complications, with the incidence of IFDs in CAR-T cell therapy recipients being measured between 0% and 10%, globally. IFDs are notorious for their potentially life-threatening nature and challenging diagnosis and treatment. In this review, we searched the recent literature aiming to examine the risk factors and epidemiology of IFDs post-CAR-T infusion. Moreover, the role of antifungal prophylaxis is investigated. CAR-T cell therapy recipients are especially vulnerable to IFDs due to several risk factors that contribute to the patient’s immunosuppression. Those include the underlying hematological malignancies, the lymphodepleting chemotherapy administered before the treatment, existing leukopenia and hypogammaglobinemia, and the use of high-dose corticosteroids and interleukin-6 blockers as countermeasures for immune effector cell-associated neurotoxicity syndrome and cytokine release syndrome, respectively. IFDs mostly occur within the first 60 days following the infusion of the T cells, but cases even a year after the infusion have been described. Aspergillus spp., Candida spp., and Pneumocystis jirovecii are the main cause of these infections following CAR-T cell therapy. More real-world data regarding the epidemiology of IFDs and the role of antifungal prophylaxis in this population are essential.